Penegakan Hukum oleh Polri Terhadap Pelaku Tindak Pidana Judi Online (Studi pada Kepolisian Sumatera Utara) - Kurniawan, M. Yundha; Siregar, Taufik; Hidayani, Sri (ARBITER: Jurnal Ilmiah Magister Hukum, 2024)
Law enforcement is carried out by law enforcers. The implementation of the law in society, apart from depending on the legal awareness of the community, is also very much determined by law enforcement officials. Law enforcement by the Indonesian National Police against perpetrators of online gambling crimes at the North Sumatra Regional Police is carried out in accordance with the provisions of Law No. 19 of 2016 on amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions. Law enforcement against perpetrators of online gambling crimes in the Police. The increasing mode of online gambling crimes is not accompanied by an increase in the quality and quantity of Polri personnel. Lack of mastery of information technology by investigators in revealing perpetrators of online gambling crimes. Lack of identity of perpetrators and lack of witnesses. Lack of evidence in the filing process. Lack of cooperation between the Police and providers and the public to obtain information related to online gambling crimes. The lack of cooperation between the Police and the Public Prosecutor in the process of investigating online gambling crimes